Telomeres stall DNA loop extrusion by condensin - Brian T. Analikwu; Alice Deshayes; Jaco van der Torre; Thomas M. Guérin; Allard J. Katan; Claire Béneut; Roman Barth; Jamie Phipps; Vittore Scolari; Xavier Veaute; Didier Busso; Karine Dubrana; et al. (Cell Reports, 2025)
Summary: DNA loop extrusion by SMC proteins is a key process underlying chromosomal organization. It is unknown how loop extruders interact with telomeres where DNA is densely covered with proteins. Using complementary in vivo and in vitro single-molecule approaches, we study how loop-extruding condensin interacts with Rap1, the telomeric DNA-binding protein of Saccharomyces cerevisiae. We show that dense linear Rap1 arrays can completely halt DNA loop extrusion, with a blocking efficiency depending on the array length and the DNA gap size between proteins. In anaphase cells, dense Rap1 arrays are found to accumulate condensin and to cause a local chromatin decompaction, as monitored with a microscopy-based approach, with direct implications for the resolution of dicentric chromosomes produced by telomere fusions. Our findings show that linear arrays of DNA-bound proteins can efficiently halt DNA loop extrusion by SMC proteins, which may impact cellular processes from telomere functions to transcription and DNA repair.